Early Metabolic Benefits of Switching Hydrocortisone to Modified Release Hydrocortisone in Adult Adrenal Insufficiency - Bannon, Christopher A. M.; Border, Daniel; Hanson, Petra; Hattersley, John; Weickert, Martin O.; Grossman, Ashley; Randeva, Harpal S.; Barber, Thomas M. (Frontiers in Endocrinology, 2021)
Purpose: To compare metabolic effects of modified release hydrocortisone (MR-HC) with standard hydrocortisone (HC) therapies in adults with Adrenal Insufficiency (AI). Methods: Adult patients (n=12) with AI, established on HC therapy, were recruited from Endocrinology clinics at University Hospitals Coventry and Warwickshire (UHCW), UK. Baseline (HC) metabolic assessments included fasting serum HbA1C, lipid and thyroid profiles, accurate measures of body composition (BodPod) and 24-hour continuous measures of energy expenditure including Sleeping Metabolic Rate (SMR) using indirect calorimetry within the Human Metabolism Research Unit, UHCW. All participants then switched HC to MR-HC with repeat (MR-HC) metabolic assessments at 3-months. Paired-sample t-tests were used for data comparisons between HC and MR-HC assessments: P-value <0.05 was considered significant. Results: Following exclusion of 2 participants, analyses were based on 10 participants. Compared with baseline HC data, following 3-months of MR-HC therapy mean fat mass reduced significantly by -3.2Kg (95% CI: -6.0, -0.4). Mean (SD) baseline HC fat mass vs repeat MR-HC fat mass: 31.9Kg (15.2) vs 28.7Kg (12.8) respectively, P=0.03. Mean SMR increased significantly by +77 Kcal/24 hours (95% CI: 10, 146). Mean (SD) baseline HC SMR vs repeat MR-HC SMR: 1,517 Kcal/24 hours (301) vs 1,594 Kcal/24 hours (344) respectively, P=0.03. Mean body fat percentage reduced significantly by -3.4% (95% CI: -6.5, -0.2). Other measures of body composition, energy expenditure and biochemical analytes were equivalent between HC and MR-HC assessments. Conclusions: In adults with AI, switching from standard HC to MR-HC associates with early metabolic benefits of reduced fat mass and increased SMR.